Determining Critical Soil pH for Grain Sorghum Production - Katy Butchee; Daryl B. Arnall; Apurba Sutradhar; Chad Godsey; Hailin Zhang; Chad Penn (International Journal of Agronomy)
Grain sorghum (Sorghum bicolor L.) has become a popular rotation crop in the Great Plains. The transition from conventional tillage to no-tillage production systems has led to an increase in the need for crop rotations. Some of the soils of the Great Plains are acidic, and there is concern that grain sorghum production may be limited when grown on acidic soils. The objective of this study was to evaluate the effect of soil pH for grain sorghum production. Potassium chloride-exchangeable aluminum was also analyzed to determine grain sorghum’s sensitivity to soil aluminum (Al) concentration. The relationship between relative yield and soil pH was investigated at Lahoma, Perkins, and Haskell, Oklahoma, USA with soil pH treatments ranging from 4.0–7.0. Soil pH was altered using aluminum sulfate or hydrated lime. Soil acidity reduced grain sorghum yield, resulting in a 10% reduction in yield at soil pH 5.42. Potassium chloride-exchangeable aluminum levels above 18 mg kg−1 resulted in yield reductions of 10% or greater. Liming should be considered to increase soil pH if it is below these critical levels where grain sorghum will be produced.